Histopathological Study of Skin Lesions in A Tertiary Care Hospital: A Cross - Sectional Study/A Retrospective Study - Dr Kirti Nishant Vyas; Dr Jyoti Prakash Sapre; Dr Nilam Hardik Patel (International Journal of Pharma and Bio Sciences, 2023)
The skin has many functions and is a complex organ. Epidermis with skin adnexa, melanocytic system, dermis and subcutis are the three main anatomic components of the skin. Skin is the body’s largest sensory organ of the body and acts asis a barrier against various harmful environmental agents. The clinical features of skin lesions are related to the underlying pathological processes. Skin conditions fall into three clinical groups (1) well-defined appearance and distribution, (2) with a characteristic pattern but with a variety of underlying clinical conditions, (3) with a variable presentation and no constant association with underlying conditions. Although dermatology is a clinical subject, an understanding of cellular changes in skin disease can give helpful insights into the pathological processes. This study was carried out to find outdetermine the frequency of various skin lesions at dermatology OPD which are also confirmed by histopathological studies. Thus histopathological diagnosis will help clinicians in managingmanage patients in terms of further requiring clinical investigations and treatment. This Furthermore, this study gives ideas about various skin lesions in correlation with age, sex and site of involvement at tertiary care hospitals and it. It will help to educate the community and physicianphysicians accordingly after the study results. A 3-year retrospective study of 120 cases was done in a tertiary care hospital, Nadiad, from 1st August 2019 to 31st August 2022. The diagnosis of these skin lesions was confirmed by histopathological examination with routine hematoxylin and eosin stain. A total of 120 cases were studied, 61 cases (50.8%) were males, and 59 cases (49.1%) were females. In males’ commonest Males’ most common lesions were granulomatous lesions, leprosy (7.5%) followed by %), and keloid lesions. In females, the commonestmost standard lesions were keloids (10.0%) and, granulomatous lesions, leprosy (5.83%). Skin biopsy is one type of integrated approach whichthat helps in increasingincrease the accuracy of diagnosis and better management of the patients.